Influence of ring traveller weight and coating on hairiness of acrylic and cotton yarns - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION, 2003)
The influence of ring-travellers of different weights, types and coatings on-hairiness of 30 tex (alpha(tex), 31.6) acrylic yarns spun from microfibres and cotton yarns has been studied. The yarns were also knitted into fabrics to observe-and evaluate pilling values. It is observed that the hairiness values of acrylic and cotton yarns decrease. as,the traveller weight increases, regardless of the type of coating used. The C2f flat travellers cause less hairiness than M2dr half round travellers. Short fibres-are found to be the main factor to cause yarn hairiness.
Keywords: acrylic yarn; cotton yarn; pilling; spinning; yarn hairiness